2002
DOI: 10.1007/s00436-001-0537-8
|View full text |Cite
|
Sign up to set email alerts
|

Traffic pathways of Plasmodium vivax antigens during intraerythrocytic parasite development

Abstract: We investigated the secretory traffic of a Plasmodium vivax antigen (Pv-148) synthesised by the parasite during the blood cycle, exported into the host cell cytosol and then transported to the surface membrane of the infected erythrocyte. Studies of the ultrastructure of erythrocytes infected with P. vivax showed that intracellular schizogony is accompanied by the generation of parasite-induced membrane profiles in the erythrocyte cytoplasm. These structures are detectable soon after the parasite invades the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The Pv-148 is synthesized by P. vivax parasites throughout the asexual development, and it becomes exported into the host cell cytosol when reaching the surface membrane of the infected erythrocyte via clefts (Bracho et al 2002). Results showed that antiflotillin-2 co-labeled the clefts and the cell surface domains where Pv-148 was present (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The Pv-148 is synthesized by P. vivax parasites throughout the asexual development, and it becomes exported into the host cell cytosol when reaching the surface membrane of the infected erythrocyte via clefts (Bracho et al 2002). Results showed that antiflotillin-2 co-labeled the clefts and the cell surface domains where Pv-148 was present (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The IgG1 monoclonal antibody (mAb) raised against flotillin-2 of human origin was obtained from BD Biosciences (San Diego, CA, USA). The IgM 7C5B71 mAb which identifies the 148-kDa P. vivax (Pv-148) protein was produced previously in our laboratory (Perez et al 1997;Bracho et al 2002).…”
Section: Primary Antibodiesmentioning
confidence: 99%
“…Blocking the assembly of the network, blocks the delivery of exogenous lucifer yellow. Findings suggest that the TVM is part of the secretory pathway involved in lipid transport across the Plasmodium infected erythrocyte 12 .…”
Section: Lipid Transport Mechanisms In Plasmodiummentioning
confidence: 97%
“…Because the mature erythrocyte has no intracellular organelles and none of the trafficking machinery used by most eukaryotic cells to transfer proteins to their correct destinations, the parasite needs to set up a completely novel system for trafficking of proteins and antigens to the surface of red blood cells [3], [4]. This system includes insertion of membrane profiles in the cytoplasm of the erythrocyte, such as membrane clefts, named Maurer's clefts in P. falciparum [5] or membrane clefts in other species such as the human parasite P. vivax [6] and rodent malaria parasite P. berghei [7], and a tubovesicular network, a term that has been introduced for a membranous network formed by projections of the parasitophorous vacuole membrane (PVM), described in P. falciparum [8], P. vivax [6] and P. berghei [7]. An association between these membranous structures with alterations on the surface of infected erythrocyte has been demonstrated by Bhattacharjee et al [9].…”
Section: Introductionmentioning
confidence: 99%